New species and records of the mite genus Prolistrophorus (Acariformes: Listrophoridae) from rodents of the subfamily Sigmodontinae (Rodentia: Cricetidae) - Bochkov, Andre V. (2014)
Six fur-mite species of the genus Prolistrophorus Fain, 1970 (Acariformes: Listrophoridae) were recorded from Central and South American rodents of the subfamily Sigmodontinae (Rodentia: Cricetidae). Among them, Prolistrophorus (Aprolistrophorus) parabidentatus sp. nov. from Akodon azarae from Argentina and Prolistrophorus (Aprolistrophorus) tylomys sp. nov. from Tylomys nudicaudus from Guatemala are described as new for science. New hosts are recorded for the following species: Prolistrophorus (Prolistrophorus) grassii (Radford, 1954) from Zygodontomys brevicauda from Colombia, P. (P.) frontalis (Hirst, 1921) from Oligoryzomys sp. from Argentina, P. (P.) argentinus (Hirst, 1921) from Melanomys caliginosus, Akodon affinis from Colombia and Scapteromys aquaticus from Argentina, Prolistrophorus (Beprolistrophorus) hirstianus Fain, 1973 from Scapteromys aquaticus from Argentina.